Development of hybrid pin-biometrics database identification and verification system: Demonstrated in automated teller machine. Issue 2 (April 2018) - H, H; O., Oyeniran R.; Saka-Balogun, Saka-Balogun; R., A.; O., Oladepo
No abstract available